Kolaborasi Pemerintah dalam Mewujudkan Transportasi Hijau di Kota Pekanbaru - Anugerah, M Fajar; Yahya, Mhd. Rafi; Widiyati, Widiyati (Innovative: Journal Of Social Science Research, 2024)
The purpose of this research is to find out how Government Collaboration in realising Green Transportation in Pekanbaru City. This research uses qualitative research methods. Types and sources of data in this study are primary data and secondary data obtained by using interviews and documentation, then analysed qualitatively. using interviews and documentation, then analysed qualitatively. The technique of determining informants using purposive sampling. The results of This research shows that the Department of Transportation has made local regulation which reads that the City Government is obliged to provide 5% of the APBD budget. APBD. The Department of Transportation has also collaborated with several parties which the Department of Transportation in cooperation with the Kawasaki Government Japan got studies on Eco transport using gas through palm oil waste. through palm oil waste. However, in realising green transport the Department of Transportation Transportation Department still has to make improvements everywhere and requires considerable investment. Programme strategies include the TUMI Mentee Cities Indonesia to realise green transportation in Pekanbaru City in this case the Transportation Agency involves the role of Government, Private and also In this case the Transportation Agency involves the role of Government, Private and also Society in realising green transport.